Pengaruh Gaya Kepemimpinan Terhadap Disiplin Kerja Karyawan Pada Kantor Kesatuan Pengelolaan Hutan Produksi Unit IV Meranti Kecamatan Tungkal Jaya - Avissa Calista; Siti Maimunah (Jurnal Manajemen Kompeten, 2020)
This study aims to determine and analyze the influence of the Leadership Style on Work Discipline at the Unit IV Meranti Production Forest Production Unit Office in Tungkal Jaya District. The research data was obtained from questionnaires, literature studies, and several direct observations according to the research objectives. The analytical method uses the Kunatitative Method with hypothesis testing, namely the t test. The number of samples was 38 employees of the Unit IV Management of Unit IV Meranti Production Forest in Tungkal Jaya District. The results showed that Leadership Style had a significant effect on Employee Work Discipline. From this study obtained the value of t test calculation obtained t count of 2.899> 2.028 then Ha is accepted and Ho is rejected, meaning there is a significant influence between X (leadership style) and Y (work discipline). Keywords: Leadership Style, Work Discipline.